Agriculturale extension and speaker acceptance: a simple cross analysis between groups at University Stage - Abd Hamid @ Ghazali, Izzah; Wan Yahaya, Wan Asrina; Rahim, Hairazi (Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2020)
Effective communication skills is one of the many abilities that agricultural extensionists should possess. This is because, these officers will be required to disseminate the latest knowledge and introduce new technologies to farmers to fulfil national agricultural policies and vision. Anxiety is a common issue faced by extensionists, especially during oral briefings or presentation and for officers who are still new at their job. The problem could arise from situational or personal effects, which play significant roles in regulating anxiety. Controlled anxiety allows for a remarkable speech delivery and accelerate audience attention and involvement. The study focused on determining the challenges or factors influencing the fluency/smoothness in giving speeches by academic and non-academic personnel in UPMKB. Both groups are irregularly involved in extension services to the Bintulu community. A semi-structured questionnaire was prepared and distributed among 30 respondents. This study used an in-depth interview and content analysis to highlight the challenges among respondents. Our findings indicated two main challenges, namely the occurrence of speech anxiety and insufficient preparation before speech delivery. Older and more experienced respondents (>16 years job experience) showed controllable anxiety compared to the younger ones due to the younger officers limited public speaking experience. The response of the audience during agricultural talks significantly affects the respondent’s anxiety by either reducing or increasing the anxiety through non-verbal communication — moreover, sufficient time to prepare the information for the speech also regulates anxiety in respondents. Therefore, invitation for agricultural extension talks or speeches must consider a speaker’s expertise and provide sufficient advance notice.